Analisis Hukum Terhadap Diskrepansi Peradilan Dalam Tindak Pidana Pengalihan Jaminan Fidusia: Studi Putusan Nomor 45/Pid.Sus/2023/PN.SMN - Alex Sukadi; Antonius Maria Laot Kian; Cecep Tedi Siswanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines judicial discrepancies in criminal cases of fiduciary transfer, focusing on Decision No. 45/Pid.Sus/2023/PN.SMN. Discrepancy is understood as the inconsistency between trial facts, the prosecutor’s evidence, and the judge’s considerations, which may lead to injustice and reduce public trust in the judiciary. The purpose of this study is to analyze the forms of discrepancy found in the decision and to assess their legal implications for the protection of the defendant’s rights and legal certainty. The research method employed is empirical juridical research with a sociological juridical approach, using statutory analysis, case studies, interviews with law enforcers, and literature review. The findings indicate disharmony in the assessment of intent (mens rea), the interpretation of written consent, and the proof of losses suffered by fiduciary recipients. Such discrepancies weaken the quality of the judgment, create legal uncertainty, and potentially violate the principle of fair trial. This study concludes that harmonization between trial facts, prosecutorial evidence, and judicial reasoning is necessary to maintain the integrity of the criminal justice system, improve the quality of judicial decisions, and strengthen legal protection for the parties involved.